CVPR 2011 2011
DOI: 10.1109/cvpr.2011.5995317
|View full text |Cite
|
Sign up to set email alerts
|

Online domain adaptation of a pre-trained cascade of classifiers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 11 publications
0
99
0
Order By: Relevance
“…Unlike other domains such as speech recognition and handwriting recognition, where adaptation has been indispensable, adaptation for visual object detection has received relatively little attention. Some early work has been conducted in this area [219,220,202,203] and we strongly believe that this is a great direction for future work. …”
Section: Discussion Future Work and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other domains such as speech recognition and handwriting recognition, where adaptation has been indispensable, adaptation for visual object detection has received relatively little attention. Some early work has been conducted in this area [219,220,202,203] and we strongly believe that this is a great direction for future work. …”
Section: Discussion Future Work and Conclusionmentioning
confidence: 99%
“…For example, how do current face detectors trained on standard databases perform in digitized images of the 19th century or in a collection of out-of-focus images from surveillance cameras for a particular environment? Instead of retraining the detectors from scratch when a new collection is available, an interesting topic of further research is to develop techniques which can adapt to a new image dataset without having access to the original training data [202]. That way camera and environment specific face detectors with very high performance could be routinely developed.…”
Section: Discussion Future Work and Conclusionmentioning
confidence: 99%
“…Hence, our main emphasis is to prove their advantage over Haar-like features that is clearly shown in Figure 9(b). Computational more complex methods like the results of Li et al [24] and Jain et al (VJGPR) [25] shown in Figure 9(b) use SURF features [24] or model inter-detection dependencies to exploit scene information [25] to derive higher detection rates. But especially Li et al [24] propose besides SURF features a AUC score for cascade training as a second contribution that also adds to their good results and is not in contrast to 2Rec-Features.…”
Section: Face Detectionmentioning
confidence: 99%
“…(Note: Background regions have been obfuscated for legal/privacy reasons) problem of domain adaptation, seeking to develop effective mechanisms to transfer or adapt knowledge from one domain to another related domain. While these advances have also been applied by the computer vision community with promising results [22,17,15,1], object models are still being trained and tested on images consisting of only one object zoomed and cropped at the center of a relatively uniform background. As a result, in such experimental settings the general problem of object detection is reduced to that of image classification.…”
Section: Introductionmentioning
confidence: 99%